THE ROLE OF GUT MICROBIOTA IN REGULATING HUMAN IMMUNE RESPONSES: IMPLICATIONS FOR PERSONALIZED NUTRITION - Dr. Sophia Zaidi; Dr Anand Prakash Verma; Dr. Smita Jadhav; Dr. Bhagyesh Kulkarni; Dr. Pradnya Karanjgaonkar; Supriyo Acharya; Dr Arun Kumar Dwivedi (The Bioscan, 2025)
Background The gut microbiota, a diverse microbial ecosystem within the gastrointestinal tract, plays a vital role in modulating immune responses and maintaining human health. Dysbiosis, or microbial imbalance, has been related to various immune-associated issues, such as inflammatory bowel ailment, allergic reactions, and autoimmune situations. Objective This paper aims to explore how gut microbiota influences human immune responses and discuss the potential of leveraging this relationship for personalized nutrition interventions. Methods This is a literature-based evaluate reading modern-day peer-reviewed studies from databases along with PubMed, Scopus, and Web of Science. Studies were decided on based on their relevance to gut microbiota-immune interactions and the role of nutrients in modulating these effects. Results Key findings show that specific microbial species enhance immune feature via metabolite manufacturing, together with brief-chain fatty acids (SCFAs). Diet composition notably alters microbial variety, influencing immune tolerance and inflammatory responses. Probiotics and prebiotics exhibit therapeutic promise in restoring microbial stability and enhancing immune regulation. Conclusion Understanding the bidirectional verbal exchange between the gut microbiota and the immune machine opens pathways for personalized nutrients strategies that could save you or manage immune-associated issues. Further medical trials are crucial to establish standardized, microbiome-informed dietary suggestions.